2022
DOI: 10.7717/peerj.13194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exergaming on executive function of older adults: a systematic review and meta-analysis

Abstract: Background Executive function (EF) involves a series of high-level processes, such as inhibition, switching, and updating. Aging-related cognitive decline has been shown to be strongly associated with EF worsening. The aims of this study were to perform a meta-analysis to evaluate the effects of exergaming, an emerging intervention, on EF performance in older adults and to conduct a moderator analysis of exergaming effects on EF. Methods Randomized controlled trials examining exergaming influences on EF in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Some preliminary studies suggested that exergaming interventions may improve these clinical outcomes in older adults when the interventions involved components that have strong effects on the outcomes concerned (e.g., incorporating cognitively stimulating games during physical exercises). 38,[43][44][45] We demonstrated a high retention and adherence of the NRFA exercise program in the participants. This suggests that our exercise program is potentially enjoyable and can motivate older adults to engage in exercise training.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Some preliminary studies suggested that exergaming interventions may improve these clinical outcomes in older adults when the interventions involved components that have strong effects on the outcomes concerned (e.g., incorporating cognitively stimulating games during physical exercises). 38,[43][44][45] We demonstrated a high retention and adherence of the NRFA exercise program in the participants. This suggests that our exercise program is potentially enjoyable and can motivate older adults to engage in exercise training.…”
Section: Discussionmentioning
confidence: 72%
“…We expected that the NRFA exercise program may have only small effects on these clinical outcomes because the program did not specifically focus on improving these outcomes. Some preliminary studies suggested that exergaming interventions may improve these clinical outcomes in older adults when the interventions involved components that have strong effects on the outcomes concerned (e.g., incorporating cognitively stimulating games during physical exercises) 38,43–45 …”
Section: Discussionmentioning
confidence: 99%
“…While one review examined only nursing home residents [ 38 ], another review [ 45 ] included only community-dwelling older adults. On the other site, while one review [ 33 ] focused only on aerobic exercise, another review [ 37 ] centered merely on resistance training, yet a third one [ 42 ] focused on exergames.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research findings have supported the potential relationship between physical activity and neural changes, indicating that MBE can modulate brain structures ( 64 ) and induce alterations in brain neural activity and functional connectivity ( 64 , 65 ), including regions such as the hippocampus ( 66 ) and prefrontal cortex ( 64 ), which play a crucial role in cognitive function. Currently, consistent observations indicate reduced structural integrity in the hippocampus and prefrontal gray matter in individuals with SCD ( 67 – 70 ), as well as a decrease in the functional connectivity between the hippocampus and prefrontal regions ( 71 , 72 ).…”
Section: Discussionmentioning
confidence: 96%